Aplicación de la presunción de inocencia en delitos de hurto simple en el distrito judicial de Lambayeque 2016 - Suyon Mio, Juan Alberto (2019)
ABSTRACT The main objective of the investigation was to determine to what extent the principle of the Presumption of Innocence has been applied in the previous trial and due process in the criminal proceedings in the Judicial District of Lambayeque. To verify the hypothesis, a sample constituted by 347 judicial files was considered for the crime of simple theft in the judicial district of Lambayeque, 10 sentences of the Constitutional Court in the period 2003-2012 on presumption of innocence; and by 50 magistrates of the Judicial Branch and Public Prosecutor of Lambayeque. Likewise, the following were reviewed: Legal doctrine books, information extracted from the internet, specialized magazines, jurisprudence and national and foreign legislation; from which the information related to the study variables was extracted, using the techniques of documentary collection, signing and survey. Once the information was obtained, it was organized and presented in frequency tables for its discussion with the historical, comparative, dogmatic, analysis and synthesis methods. The conclusions reached were that in the Judicial District of Lambayeque, if the Principle of Presumption of Innocence is respected and applied largely (as a fundamental guarantee of the accused), the prior trial and due process will be carried out. As that the crime of simple theft, constitutes the basic criminal type of greater incidence of the crimes against the Patrimony.